Impact of Liquidity and Activities on Profitability by Mediation of Capital Structure: Empirical Evidence from Sri Kehati Indexed Companies - Dede Suharna; Augustina Kurniasih (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This paper analyzes the impact of liquidity and activity on profitability with capital structure as a mediating variable. Return on assets (ROA) is the company's ability to generate profits in a certain period and develop dynamically that changes from time to time, depending on the variables that affect it as a whole, type of business, or company. This study contributes to the literature by investigating the factors that affect the profitability (ROA) of companies indexed by SRI KEHATI. This study aims to identify the determinants of company profitability either directly or through the role of mediating variables. The analysis used is panel data regression. The selected model is the fixed effect model (FEM) and uses path analysis and Sobel test. The results show that the current ratio has a direct effect on capital structure and capital structure has a direct effect on ROA. On the other hand, the current ratio and working capital turnover have no direct effect on ROA and working capital turnover does not directly affect the capital structure. The results of the path analysis prove that the capital structure is able to mediate the effect of the current ratio on ROA.